Multidimensional Approach of Job Performance: Toward a Prediction Model - Tutu, Andreea (Richtmann Publishing, 2012)
This paper investigated the interacting effect of the employee’s job competency, extra-role performance and three persistencefactors (current purposes pursuing - CPP), recurrence of unattained purposes - RUP, and long term purposes pursuing - LTPP) on thejob performance of a sample of 200 Romanian employees (participation rate: 86.2%). We used correlation analysis, prediction models,and, as tools, competency assessment checklists developed by means of the Competency Elicitation Interview (Faix et al., 1991),Robertson’s performance scales for job performance (1996, 1997), Smith’s scale for extra-role performance (1983) and a persistencescale (Constantin, 2010). Results support the idea that job performance can be approached from a multidimensional point of view. Thesignificance of extra-role performance and two persistence factors (current purposes pursuing-CPP, and long term purposes pursuing-LTPP) was successfully established, highlighting the important role they have in relationship with job performance, as valid predictors ofsupervisory ratings of employees’ performance. Furthermore, job competencies alone seem to be necessary but not sufficient to predicthigh levels of job performance. Main limitations (such as those who refused to participate they didn’t had comparable demographics withthose who agreed to participate) along with main findings are being discussed.